Experimental measurements of the detection performance of cyclostationarity-based spectrum sensing - Bating, Carlos B.
Cyclostationarity-based spectrum sensing exploits the spectral correlation features of a primary user (PU) signal for detection. This detection method is robust against noise and interference. However, the existing studies on cyclostationarity-based detection focused on analytical and simulation approach. The purpose of this work is to determine the experimental performance of cyclostationarity-based spectrum sensing using magnitude squared coherence (MSC) function. MSC is the magnitude square of the function that measures the intensity of coherence of the PU signal spectral components. A testbed for MSC-based detection was implemented on National Instruments Peripheral Component Interconnect Extensions for Instrumentation (NI PXI) platform and FFT Accumulation Method (FAM) was adopted to measure the MSC of the PU signal which is modelled as real BPSK and real QPSK signal. This work focused on characterizing the effect of PU duty cycle and the effect of the time-frequency resolution product (TFRP) parameter of FAM to the empirical performance of MSC-based detection. Resulsts show that the experimental performance of MSC-based detector deteriorates with decreasing PU duty cycle which agrees with existing simulation study. Moreover, the empirical performance degrades with decreasing TFRP which agrees with the theoretical reliability condition requiring a TFRP of much greater than unity. Furthermore, it was observed that MSC-based detection has an experimental performance gain of around 6 dB over energy detection scheme which is in similar trend with simulation studies.